A Randomised Controlled Trial to Determine the Effect of Unique Grain Fibre-Fortified Bread on Gastrointestinal Symptoms, General Wellbeing and Mental Health of Healthy Adults - Hwei Min Ng; Jasjot Maggo; Catherine Louisa Wall; Simone Birgit Bayer; Nicole Clemence Roy; Richard Blair Gearry (Proceedings)
Background: High dietary fibre (DF) intake may have beneficial effects on gastrointestinal and brain interactions. Bread is an ideal vehicle to incorporate grain fibre to increase DF content. To date, no studies have explored the association between a habitual intake of bread fortified with unique grain fibre and gastrointestinal symptoms, general wellbeing, and mental health. Objective: To determine whether a four-week intake of bread fortified with unique grain fibre (thrice the amount of DF than control bread) improves subjective gastrointestinal symptoms, general wellbeing, and mental health compared to baseline and white toast (control bread) in healthy adults with low DF intake. Methods: A four-week, two-armed, placebo-controlled, double-blinded, randomised crossover study separated by a two-week washout period was conducted. Fifty-six participants with low DF intake (<18 g/day for females, <22 g/day for males) consumed three (females)/four (males) slices of fortified bread daily for four weeks then control bread and vice versa. Before and after each intervention phase, the participants completed seven self-reported questionnaires: the Gastrointestinal Symptom Rating Scale, Patient-Reported Outcome Measurement Information System-Anxiety and Depression Short Forms 8a, World Health Organisation Well-Being Index, Warwick-Edinburgh Mental Wellbeing Scales, Multidimensional Fatigue Inventory Short Form, and the Subjective Vitality Scale. Results: Fifty-five participants completed all of the questionnaires before and after each intervention. The preliminary and blinded results showed no significant changes (all p > 0.05) in gastrointestinal symptoms, general wellbeing, and mental health following intervention and between interventions. Discussion: With thrice the amount of DF, the unique grain fibre-fortified bread did not cause gastrointestinal symptoms nor did it worsen general wellbeing and mental health in healthy adults with low DF intake. Encouraging the consumption of unique grain fibre-fortified bread could still be an acceptable and effective method to improve DF intake in a healthy adult population with low DF intake. Trial Registration: ACTRN12622000884707.